Comparison of hybridizing options for solar heat, biomass and heat storage for electricity generation in Spain. (15th October 2020) - Hussain, C.M. Iftekhar; Norton, Brian; Duffy, Aidan
Highlights: Techno-economic parameters for hybrid solar-biomass power plants are compared. For comparative analysis, parameters are obtained through simulation. Levelized cost of electricity is calculated using simulation results. Simulated cost of electricity is validated by previous relevant literatures. Best economically viable system is identified using validated simulation results. Abstract: Diurnal and seasonal variations of direct solar energy circumscribe locations suitable for sole use of concentrated solar power for electricity generation, whereas to generate electricity at night and during winter months, biomass systems can be used that incur fuel expenditures and may encounter fuel supply discontinuities. Combining solar heat, biomass conversion and heat storage in a hybrid electricity generation plant may overcome the limitations of sole use of any one of these energy sources in specific geographic and/or economic conditions. In this work standalone biomass, hybrid concentrated solar power-biomass and hybrid concentrated solar power-biomass-thermal energy storage power generation systems are simulated. With an 80% plant capacity factor for each power plant configuration, levelized cost of electricity is calculated using the simulated fuel consumption. In a comparative analysis, the hybrid concentrated solar power-biomass power plant is found to be an economically viable option having 25% lower levelized cost of electricity compared to a hybrid concentrated solar power-biomass- thermal energy storage power plant in a particular scenario considered.